Primary Tumor Resection Improves Survival for EGFR-TKI-Treated Patients With Occult M1a Lung Adenocarcinoma - Fu, Fangqiu; Wen, Zhexu; Gao, Zhendong; Zhao, Yue; Li, Yuan; Zhang, Yang; Chen, Haiquan (Frontiers in Oncology, 2021)
Background: The role of primary tumor resection in occult M1a lung adenocarcinoma remains unclear, especially for patients receiving targeted therapy. The purpose of this study is to assess the effect of primary tumor resection on overall survival (OS) in lung adenocarcinoma patients with occult pleural disseminations receiving targeted therapy. Methods: Lung adenocarcinoma patients with intraoperatively-confirmed occult pleural dissemination (M1a), who hospitalized in the Department of Thoracic Surgery in Fudan Shanghai Cancer Center from May 2008 to December 2017 and received EGFR-TKIs therapy, were enrolled. Log-rank tests were used to compare the survival differences between groups. Results: 34 patients receiving EGFR-TKIs were enrolled. The majority of them were never smokers (29/34, 85.3%). Among the enrolled patients, 20 (58.8%) patients underwent primary tumor resection, while 14 (41.2%) patients not. There was no distributional difference of baselines between patients undergoing and not undergoing primary tumor resection. Further analyses demonstrated that the patients undergoing primary tumor resection had a prolonged OS compared with those not (log-rank P= 0.042). The 2-year and 5-year OS for patients receiving primary tumor resection and EGFR-TKIs was 90.0% and 60.1%. Conclusions: Primary tumor resection was associated with improved survival in patients with occult intraoperatively-confirmed M1a adenocarcinoma receiving EGFR-TKIs.